A SYSTEMATIC REVIEW ON APPLICATION OF NANOTECHNOLOGY FOR THE INSECT PEST MANAGEMENT (International Journal of Food and Nutritional Sciences, 2022)
Nanotechnology is a promising field of interdisciplinary research. It provides up prospects in the areas of medicine, electronics, agriculture, and insecticides. The uses of nanotechnology are quite diverse. Among these is the use of nanomaterials for the management of insect pests. The use of chemical pesticides, which are harmful to people, animals, and the fertility of the soil, renders integrated pest management ineffective. Without having a negative impact on the environment, nanotechnology can one day provide environmentally friendly and efficient methods for the management of insect pests in agriculture. This painting focuses on traditional means to managing insect pests as well as the potential of using nanomaterials in such management as a modern use of nanotechnology.Pesticides increase the productivity of agriculture, but their misuse can contaminate both the environment and the food supply. Improvements to pesticide delivery systems can increase bioefficacy while minimizing negative effects on the environment and human health. In modern insect pest management, nanoparticles are used as an effective tool. The efficiency of nanopesticides at low concentrations is beneficial to farmers and helps decrease pollution. This article provides a systematic review of traditional approaches to the management of insect pests as well as the potential of nanomaterials in the context of contemporary nanotechnology-based insect pest control